Non-recurrent right laryngeal nerve identified during endoscopic thyroidectomy via areolar approach: a case report - Jin, Xiaohu; Yuan, Ronghua (Frontiers in Surgery, 2023)
Background: Nonrecurrent laryngeal nerve (NRLN) is a rare but significant anatomical variation in thyroid surgery, and lack of awareness of NRLN may lead to intraoperative injury. Here, we report a clinical case of NRLN discovered during endoscopic thyroid surgery via total areola approach in a 23-year-old female patient.Case presentation: A 23-year-old female patient presented with bilateral thyroid nodules for three years. She underwent bilateral thyroid nodule fine-needle aspiration biopsy and BRAF gene testing at our hospital, with results indicating bilateral papillary thyroid carcinoma and positive BRAF gene V600E mutation. Neck-enhanced CT revealed bilateral thyroid nodules and the right subclavian artery branching from the aortic arch on the distal side of the left subclavian artery. The patient underwent endoscopic thyroidectomy via total areola approach for radical resection of bilateral thyroid cancer. Intraoperatively, NRLN was found on the right side and RLN on the left side. The surgery was successful, and no postoperative complications were observed.Postoperative pathology confirmed bilateral papillary thyroid carcinoma.Although NRLN is a rare occurrence, clinicians should not overlook its presence to prevent serious complications. Preoperative imaging confirmation of the presence or absence of an abnormal subclavian artery course is crucial in preventing the sudden discovery of NRLN during surgery. Endoscopic thyroid surgery via total areola approach is a safe and effective technique but requires a high level of professional skills and an understanding of anatomical variations to prevent nerve injury.